Prevention of menstrual toxic shock syndrome by French health professionals Running head: Toxic shock syndrome prevention - Anne-Claire Schmautz; Gérard Lina (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Objectives: To appreciate the education on the use of intimate protection products and the prevention of menstrual toxic shock syndrome by French health professionals. Methods: Fourteen semi-structured interviews with health professionals involved in women's health (midwives, school nurses, general practitioners, and obstetrician-gynecologists) were conducted over a period of six months (March 2019 to September 2019) in the Ile-de-France region in France. Their ages ranged from 26 to 67 years. All the interviews were recorded and typed to extract a qualitative analysis. Results: The healthcare professionals interviewed surveyed report little involvement in educating their patients about intimate protection products and the prevention of menstrual toxic shock syndrome. Conclusion: It would seem useful to increase the awareness of the healthcare professionals involved of the importance of educating their patients about the proper use of intimate protection products. The aim is to prevent the occurrence of infectious pathologies, particularly menstrual toxic shock syndrome the main microbiological risk identified as being associated with the misuse of internal intimate protection products.